Preparação e caracterização de blendas poliméricas a base de manipueira - Iurckevicz, Genice (2011)
The manipueira, liquid residue generated in industrial process of cassava is stored in stabilization lake and after discarded in water resources. To reduce the impacts caused by the residue of high pollution potential, it’s studied various application opportunities, as use in animal feed, production of pesticides, fertilizers, ethanol, cleaning products, vinegar and bricks (SILVA, 2009). The alternative proposed on this study is use the residue in production of biodegradable polymers, option to substitute synthetic polymers, in order to minimize the environmental impacts caused by them. The biodegradable polymers can be degraded by microorganisms as bacteria, fungi and algae. The interest in obtaining new polymer blends, cheaper and more innovative is growing, especially when considers that these products cause less environmental impact. The residue was characterized according the content of ash, total solids and sedimentable, total nitrogen, minerals, to evaluate its potential use as feedstock in the production of biodegradable polymer. This study proposes the use of manipueira in the production of polymer blends, by the method of casting with addition plasticizers / additives: polyvinyl alcohol (PVA) and glycerin, in order to improve the properties of the films, giving the polymer matrix different characteristics existing without the addition of the same. After polymer blends production were made studies to observe the behavior of the films on moisture, with tests of water absorption, permeability to water vapor and tumescence.